Listening to the voice of the market : how to increase market share and satisfy current customers - Reidenbach, R. Eric (CRC Press, 2010)
"In this book, the author teaches you how to identify and capture the Voice of the Market and then use that data, and a new understanding of it, to make your organization market-focused. It is not about hijacking customers with one-time special pricing. Instead, it is about applying the proper tools and processes to move your organization from a production or sales orientation to a truly market-based focus."--BOOK JACKET.